Evaluation of the protective effects of gossypin for ischemia/reperfusion injury in ovary tissue - Dincer, Busra; Cinar, Irfan; Yayla, Muhammed; Toktay, Erdem (Wiley, 2021)
AbstractAimOvarian ischemia–reperfusion (I/R) injury is a serious gynecological condition that affects women of reproductive age and reduces ovarian reserve. Management of I/R injury with detorsion causes reperfusion damage, in which oxidative stress plays a central role. This study aimed to investigate whether the gossypin (GOS) with antioxidant properties, a flavonoid, has beneficial effects on the biochemical, molecular, and histopathological aspects of ovarian I/R injury.MethodsThirty‐three female Balb/c mice were randomly divided into five groups as follows: Healthy (Sham‐operated control group), I/R (IR group), I/R + GOS 5 (I/R with GOS 5 mg/kg), I/R + GOS 10 (I/R with GOS 10 mg/kg), and I/R + GOS 20 (I/R with GOS 20 mg/kg). This was followed by 3 h of ischemia and subsequent reperfusion for 3 h after detorsion was exposed. GOS was injected 2 h before reperfusion.ResultsIL‐1β, IL‐6, TNF‐α, NF‐κB, and CASP‐3 mRNA expressions, SOD (superoxide dismutase) activity, GSH (glutathione), and MDA (malondialdehyde) levels, and histopathological changes were evaluated in ovarian tissue. Histological examination indicated that treatment of ovarian I/R injury with GOS led to the improvement of ovarian tissue, which was accompanied by an increase in SOD activity and GSH level and a decrease in MDA level, NF‐κB, TNF‐α, IL‐1β, and IL‐6 expressions. GOS was also corrected by reducing the elevated expression of CASP‐3 as apoptosis‐change marker.ConclusionThese findings indicate that the treatment of GOS may be useful as a conservative approach to reverse I/R injury via amelioration of oxidative stress parameters and histopathological scores, attenuation of inflammation, and the suppression of apoptosis.
Keywords: Flavonoids; Ovary; Antioxidants; Rats; Mice; Oxidative Stress; Ischemia; Malondialdehyde; Reperfusion Injury; Animals; Female; Rats, Wistar; 3. Good health